Familie, Partnerschaft, Bildung und berufliche Situation bei Patientinnen mit Anorexia nervosa: Sekundäranalyse der ANTOP-Stichprobe - Teufel, Martin; Wild, Beate; Herzog, Wolfgang (Psychotherapeut, 2017)
The influence of family, partnership, education and occupational situation on the onset and maintenance of anorexia nervosa has been widely discussed. Even in the first descriptions of the disease detailed reference was made to the dimensions of the family system. Nevertheless, the evidence on the effect of these variables on the course of the disease is still unclear. Randomized, controlled studies on the effect of psychotherapy provide little information about how these variables are distributed among participating patients and especially what influence they have on the outcome of the studies. The aim of this study was a detailed characterization of participants of the worldwide largest outpatient therapy study, the anorexia nervosa treatment of outpatients (ANTOP) study with respect to the relevance of family, partnership and the occupational situation on treatment success. The results show indications that patients in the ANTOP study have a higher education level compared to the average age-matched German population. At the same time, they appear to be less frequently in an institutionalized partnership. There were no differences in professional activity and occupation. Variables on family, partnership, education and job situation had no predictive value for weight-related treatment outcome in the ANTOP study.
Gesehen am 04.04.2018